2015
DOI: 10.1097/igc.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Groin Treatment Modality and Sequence on Clinically Significant Chronic Lymphedema in Patients With Vulvar Carcinoma

Abstract: Clinically significant CL was not different between treatment modalities in this study, but is underpowered. The results provide valuable information about treatment complications that will be useful for patient-centered counseling. Prospective evaluation of CL and its impact on quality of life is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Conversely, in the study of Gould et al lower body lymphedema was neither predicted by early complications nor by other factors (use of antibiotics, adjuvant therapy, drainage) (59). The rates of lymphedema were not significantly different according to treatment modalities (single, combination or sequence) in the study of Berger et al (60). According to some authors preserving the saphenous vein during inguinal lymphadenectomy is associated with a lower risk of lymphedema (61), but this approach is not widely accepted.…”
Section: Incidencementioning
confidence: 57%
“…Conversely, in the study of Gould et al lower body lymphedema was neither predicted by early complications nor by other factors (use of antibiotics, adjuvant therapy, drainage) (59). The rates of lymphedema were not significantly different according to treatment modalities (single, combination or sequence) in the study of Berger et al (60). According to some authors preserving the saphenous vein during inguinal lymphadenectomy is associated with a lower risk of lymphedema (61), but this approach is not widely accepted.…”
Section: Incidencementioning
confidence: 57%
“…Vulvar cancers, compared with other gynecologic malignancies, have a more reliable and predictable lymphatic drainage to the inguinofemoral nodal basins. Rates of lower extremity lymphedema after inguinofemoral lymphadenectomy range from 10% in retrospective reports43 to 73% in studies assessing patient-reported symptoms 8. In studies using a uniform methodology to diagnose lower extremity lymphedema across types of malignancy, the rates are consistently highest in vulvar cancer: based on a recent meta-analysis, the pooled incidence is 28.8% 5 39 44.…”
Section: Secondary Lymphedema In Gynecologic Malignanciesmentioning
confidence: 99%
“…In studies using a uniform methodology to diagnose lower extremity lymphedema across types of malignancy, the rates are consistently highest in vulvar cancer: based on a recent meta-analysis, the pooled incidence is 28.8% 5 39 44. This is mostly, but not entirely, related to inguinofemoral lymphadenectomy 43. Berger et al reported that 6.7% of patients with vulvar cancer treated with radiation alone developed chronic lower extremity lymphedema 43.…”
Section: Secondary Lymphedema In Gynecologic Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, standard of care for vulvar cancer is surgical treatment with vulvectomy or wide radical excision of the primary tumor +/-complete inguinal lymph node dissection (ILND). However, ILND is often accompanied by surgical complications such as impaired wound healing, acute infections, and lymph edema [3,4]. Even with advanced surgical techniques [5], more than half of the patients are affected by post-operative complications.…”
Section: Introductionmentioning
confidence: 99%